In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Liraglutide affects mitochondrial function and histone acetylation through the NQO1/SIRT3 pathway in diabetic kidney disease - Jie Gao; Xiaoyu Lv; Pingping Zhao; Bingjing Pan; Jingfang Liu (Molecular and Cellular Biochemistry, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Pupil dynamic adaptation in response to environmental luminance: A controlled laboratory study - Qing Pan; Shoujie Zhang; Jingfang Bian; Tao Luo; Minchen Wei; Peng Xue; Jingchao Xie; Jiaping Liu (Building and Environment, 2026)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

In situ construction "Metabolism-Immunity" crosstalk rewiring bioreactor with single-dose mitochondria energizing hydrogel for amplifying T cell fitness and anti-tumor immunity - Hongting Liu; Xinping Luo; Honghao Sun; Jingfang Pan; Siqian Ding; Zhanwei Zhou; Minjie Sun (Chemical Engineering Journal, 2025)

SIRT3: A Potential Target of Different Types of Osteoporosis - Binjing Pan; Chongyang Chen; Yangting Zhao; Jing Cai; Songbo Fu; Jingfang Liu (Cell Biochemistry and Biophysics, 2024)

Increased greenhouse gas emissions intensity of major croplands in China: Implications for food security and climate change mitigation - Jingting Zhang; Hanqin Tian; Hao Shi; Jingfang Zhang; Xiaoke Wang; Shufen Pan; Jia Yang (Global Change Biology, 2020)
Balancing crop production and greenhouse gas (GHG) emissions from agriculture soil requires a better understanding and quantification of crop GHG emissions intensity, a measure of GHG emissions per unit crop production. Here we conduct a state‐of‐the‐art estimate of the spatial‐temporal variability of GHG emissions intensities for wheat, maize, and rice in China from 1949 to 2012 using an improved agricultural ecosystem model (Dynamic Land Ecosystem Model‐Agriculture Version 2.0) and meta‐analysis covering 172 field‐GHG emissions experiments. The results show that the GHG emissions intensities of these croplands from 1949 to 2012, on average, were 0.10–1.31 kg CO 2 ‐eq/kg, with a significant increase rate of 1.84–3.58 × 10 –3 kg CO 2 ‐eq kg −1 year −1 . Nitrogen fertilizer was the dominant factor contributing to the increase in GHG emissions intensity in northern China and increased its impact in southern China in the 2000s. Increasing GHG emissions intensity implies that excessive fertilizer failed to markedly stimulate crop yield increase in China but still exacerbated soil GHG emissions. This study found that overfertilization of more than 60% was mainly located in the winter wheat–summer maize rotation systems in the North China Plain, the winter wheat–rice rotation systems in the middle and lower reaches of the Yangtze River and southwest China, and most of the double rice systems in the South. Our simulations suggest that roughly a one‐third reduction in the current N fertilizer application level over these “overfertilization” regions would not significantly influence crop yield but decrease soil GHG emissions by 29.60%–32.50% and GHG emissions intensity by 0.13–0.25 kg CO 2 ‐eq/kg. This reduction is about 29% and 5% of total agricultural soil GHG emissions in China and the world, respectively. This study suggests that improving nitrogen use efficiency would be an effective strategy to mitigate GHG emissions and sustain China's food security.